PENERAPAN MODEL PEMBELAJARAN VAN HIELE PADA MATERI HUBUNGAN GARIS DAN SUDUT DI KELAS VII SMP MUHAMMADIYAH 1 PALU - Fitriani Fitriani; Muh. Hasbi; Bakri Bakri (Universitas Tadulako, 2020)
Abstract: The purpose of this study is to describe the application of the Van Hiele learning model that can improve student learning outcomes in the material relationship lines and angles in class VII Muhammadiyah Middle School 1 Palu. This type of research is classroom action research (CAR). The design of the study was based on the research design of Kemmis and Mc. Taggart consists of four components, namely (1) planning, (2) action, (3) observation, and (4) reflection. This research was conducted in two cycles. The research subjects were seventh grade students of Muhammadiyah Middle School 1 Palu in the 2017/2018 school year, totaling 25 students. Data collection techniques in this study were observation, tests, interviews, and field notes. The results showed that the application of the Van Hiele learning model could improve student learning outcomes by following the phases of Van Hiele's learning model, namely: (1) inquiry, (2) directed orientation, (3) description, (4) free orientation, and ( 5) integration. In the first cycle the percentage of classical learning completeness was 47.83% and in the second cycle the percentage of classical learning completeness increased to 86.96%. In addition, the results of observations of teacher activities in managing learning in the first cycle and second cycle are in the very good category. The results of observations of student activities in following the learning process in the first cycle are in the good category and the second cycle is in a very good category.